Cough Education is Effective for Parental Independence in Overcoming Children's Cough - Lontaan, Anita; Ariando Salomon, Glendy; Ayu Rahmadani , Risna; Anggeraeni, Anggeraeni; Achmad, Viyan Septiyana (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2023)
Coughing is one of the common health problems experienced by children. Although in many cases coughing is the body's natural response to infection or respiratory tract irritation, for parents, coughing in children is often a source of worry and anxiety. The method of activities is carried out by interactive and participatory, information communication and education. The result of dedication is that education is very effective in increasing knowledge for parents or the community in the independence of parents to overcome children's coughs. It can be concluded that educational activities about overcoming children's cough have proven to be very effective in increasing the knowledge and independence of parents or the community. With an interactive approach, strong relevance, and measurable outcomes such as increased confidence and coping skills with children's health issues, the program has a real positive impact